High-capacity and long-cycle graphite negative electrode material and preparation method thereof

By mixing the medium sulfur coke and ordinary commercial coke according to a specific proportion, pre -carbonization and graphitization are prepared, and a high -capacity and long cycle of graphite negative materials are prepared, which solves the problem of decline in circulating performance in the existing technology. It has the effect of high capacity and long cycle.

CN119361692APending Publication Date: 2025-01-24WANXIANG 123 CO LTD

Patent Information

Application Number
CN202410091899.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing energy-storage graphite materials increase capacity, their circulation performance is affected and cannot meet the needs of high capacity and long circulation.

Method used

By mixing the medium sulfur coke and ordinary commercial coke according to a specific ratio, the pre -carbonization and graphization are prepared, and a graphite negative material with a long capacity and long cycle is prepared.

Benefits of technology

It achieves high capacity and long cycle performance of graphite anode materials, improves processing performance and compaction, and improves the yield of battery core production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004677132030000071
    Figure BDA0004677132030000071
  • Figure BDA0004677132030000081
    Figure BDA0004677132030000081
Patent Text Reader

Abstract

The invention relates to the technical field of graphite negative electrode materials, and discloses a high-capacity and long-cycle graphite negative electrode material and a preparation method thereof, and the preparation method comprises the following steps: (1) respectively pre-carbonizing medium sulfur coke and commercial coke; (2) mixing the pre-carbonized medium sulfur coke and commercial coke, and graphitizing to obtain a graphitized crude product; the mixing mass ratio of the medium sulfur coke to the commercial coke is (10-90%): (10-90%), and the total mass percentage is 100%; and (3) screening and demagnetizing the graphitized crude product to obtain the graphite negative electrode material. The graphite negative electrode material is obtained by compounding the medium-sulfur coke and the common commercial coke in a specific proportion, the medium-sulfur coke and the common commercial coke can play an excellent synergistic effect, and through mutual influence among limited parameters in a two-component mixing process, excellent cycle performance of the material is ensured, processability of the material is improved, and industrial application is further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphite negative electrode materials, and in particular to a graphite negative electrode material with high capacity and long cycle time and a preparation method thereof. Background Art

[0002] In recent years, the demand for lithium-ion battery energy storage has been growing, and with the increasingly higher technical requirements for energy storage cells, the energy density and long cycle requirements have increased. As for the negative electrode, some customers have demanded a capacity of more than 350mAh / g, while the previous mainstream energy storage graphite was generally 340-345mAh / g. The compaction requirement has increased from the previous 1.4-1.45g / cc to the current 1.55-1.6g / cc, and the cycle performance has increased from more than 6,000 cycles to the current more than 8,000 cycles, or even 10,000 to 12,000 cycles.

[0003] At present, energy storage graphite generally uses ordinary commercial coke from petroleum as raw material, which is graphitized after coke is bonded and granulated. The capacity of this type of graphite is generally around 345mAh / g, and the cycle performance is around 6000 cycles. To further increase the capacity of the material, it is necessary to increase the graphitization degree of the material. At this time, the cycle performance of the graphite will be seriously affected and cannot meet customer needs. Therefore, it is necessary to propose a new solution to increase the capacity of energy storage graphite and maintain the cycle performance.

[0004] Patent CN107039654A discloses a method for preparing a high-capacity, long-cycle artificial graphite negative electrode material, which includes the following preparation steps: (1) raw material shaping; (2) first mixing; (3) heat treatment; (4) graphitization; (5) second mixing; (6) carbonization heat treatment. The patent has a simple process and a high yield. It adopts shaping, liquid phase coating modification, graphitization and other methods. The product has high charge and discharge efficiency and PC resistance; the tap density of the product is improved, and the button battery made of the negative electrode material has excellent comprehensive performance. However, the material prepared by this method is a carbon-coated product. On the one hand, the cost has increased, and the cost-effectiveness of use in the energy storage field is not high. On the other hand, the high-temperature performance is poor, which is not conducive to the long-term full-charge storage of energy storage cells. Patent CN106169582B discloses a method for producing a natural needle coke composite graphite negative electrode material, which uses needle coke as raw material A, natural graphite as raw material B, asphalt powder as raw material C, graphene conductive agent as raw material D, and carbon nanotubes as raw material E. After a series of mechanical processing, surface modification, chemical deep modification, and doping methods, a negative electrode material with long cycle life, fast charge and discharge rate, good high and low temperature performance, and good processing performance is prepared, which is suitable for power batteries. The production process is simple, the production efficiency is high, the processing process is safe, and it can be used for industrial production. However, the natural graphite and needle coke raw materials used in this method do not have particularly excellent cycle performance, and are suitable for use in power batteries but cannot meet the cycle requirements of energy storage projects.

[0005] Patent CN115872398A discloses a method for producing single-granular negative electrode materials from medium-sulfur coke and its production steps: heating and calcining the medium-sulfur coke, cooling the calcined medium-sulfur coke, crushing and screening the crushed medium-sulfur coke to obtain medium-sulfur coke powder, and obtaining single-granular negative electrode materials, thereby improving the production efficiency of product graphitization and ensuring the production quality of the product, making it have a higher charge and discharge capacity and charge and discharge efficiency, and optimizing the electrical properties of graphite negative electrode materials. However, due to the high sulfur content, the medium-sulfur coke raw material has more defects after graphitization, and its processing performance and high-temperature performance are worse than those of ordinary commercial coke graphite, and it cannot be used alone in energy storage projects. Summary of the invention

[0006] In order to solve the above-mentioned technical problems, the present invention provides a high-capacity and long-cycle graphite negative electrode material and a preparation method thereof. The graphite negative electrode material is prepared by graphitizing a mixture of a medium-sulfur coke raw material and an ordinary commercial coke raw material. The medium-sulfur coke raw material is easy to graphitize, has good capacity and high compaction rate, and excellent cycle performance. The ordinary commercial coke graphite further improves the cycle performance and ensures the processing performance of the negative electrode, so as to improve the yield of battery cell production and facilitate industrial application. The material is mainly used in energy storage batteries.

[0007] The purpose of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a high-capacity and long-cycle graphite negative electrode material, comprising the following steps: (1) Pre-carbonizing medium-sulfur coke and commercial coke respectively; (2) mixing the pre-carbonized medium-sulfur coke and commercial coke, and graphitizing them to obtain a crude graphitized product; the mixing mass ratio of the medium-sulfur coke and the commercial coke is 10-90%:10-90%, and the total mass percentage is 100%; (3) Screening and demagnetizing the graphitized crude product to obtain a graphite negative electrode material.

[0008] The graphite negative electrode material obtained by the present invention is a single-particle graphite of petroleum coke. The petroleum coke used is a mixture of a certain proportion of medium-sulfur coke and ordinary commercial coke. Before mixing, the two coke sources are crushed and pre-carbonized respectively to remove excess volatiles to ensure graphitization safety. The medium-sulfur coke in the material mainly plays a role in improving the capacity and dynamic performance of the material. The medium-sulfur coke is easy to graphitize and can improve the capacity of the material. However, due to the high sulfur content, the material has more mesoporous structures after graphitization, poor processing performance, and low efficiency, resulting in poor circulation. Ordinary commercial coke can further improve the material's circulation performance and improve the material's processing performance. The application field of this graphite is energy storage batteries.

[0009] Preferably, the mixing mass ratio of the medium-sulfur coke and the commercial coke is 30-70%:30-70%, and the total mass percentage is 100%.

[0010] Preferably, the pre-carbonization temperature is 300-1000° C., and the temperature is kept for 1-5 hours.

[0011] Preferably, the graphitization temperature is 2500-3000° C., and the graphitization time is 10-30 days.

[0012] Preferably, the particle size of the medium-sulfur coke is normally distributed, and the median particle size D50 is 8.0 to 20.0 μm.

[0013] The higher the sulfur content of medium-sulfur coke, the higher the pore structure of the material, the larger the specific surface area, and the worse the processing performance.

[0014] Preferably, the particle size of the commercial coke is normally distributed, and the median particle size D50 is 8.0 to 20.0 μm.

[0015] If the particle size is too small, it will not be conducive to capacity improvement and the processing performance will deteriorate. If the particle size is too large, the rate performance and energy efficiency will be poor and the cycle will be affected.

[0016] Preferably, in step (2), the particle size of the pre-carbonized medium-sulfur coke and the commercial coke after mixing is normally distributed, and the median particle size D50 is 8 to 14 μm, more preferably 12 to 14 μm.

[0017] The particle sizes of the two can be different, but it is necessary to ensure that the particle sizes are normally distributed after mixing, and the median particle size is preferably between 8-14 μm. Preferably, the pre-carbonized medium-sulfur coke and commercial coke are mixed for 0.5 to 2 hours.

[0018] Preferably, the commercial coke is petroleum coke, coal-based coke, isotropic coke or pitch coke. In a second aspect, the present invention provides a graphite negative electrode material obtained by the above preparation method.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention obtains a graphite negative electrode material by compounding medium-sulfur coke and ordinary commercial coke in a specific ratio. The two can exert an excellent synergistic effect, improve the cycle performance of the material and improve the processing performance of the material, especially improve the compaction and roller sticking conditions, and improve the yield rate; (2) Before mixing, the two coke sources are crushed and pre-carbonized respectively to remove excess volatiles to ensure graphitization safety; (3) Since the present invention is a two-component composite, the particle size, mixing ratio, pre-carbonization and graphitization reaction conditions of the two components will have a significant impact on the performance of the graphite negative electrode material. The mutual coordination between the various limited parameters ensures the excellent processing performance and cycle performance of the material, and further expands its industrial application. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto: The preparation of high capacity and long cycle graphite negative electrode materials includes the following steps: (1) medium-sulfur coke (sulfur content 1-3%) and commercial coke (petroleum coke, coal-based coke, isotropic coke or asphalt coke) are crushed in a mechanical mill to a median particle size D50 of 8.0 to 20.0 μm; (2) Pre-carbonizing the crushed medium-sulfur coke and commercial coke respectively at a temperature of 300 to 1000° C. for 1 to 5 hours, and removing excess volatiles by pre-carbonization to ensure graphitization safety; (3) The pre-carbonized medium-sulfur coke and commercial coke are mixed in a mixer at a mass ratio of 10-90%: 10-90% and a total mass percentage of 100% for 0.5-2 hours. The particle size after mixing is normally distributed, and the median particle size D50 is 8-14 μm. This particle size range can make the synergistic effect and dispersion effect between the medium-sulfur coke and the commercial coke better, thereby better improving the compaction and roller sticking conditions. (4) transferring the mixed coke source into a graphitization furnace for graphitization at a temperature of 2500 to 3000° C. for a graphitization time of 10 to 30 days to obtain a crude graphitized product; (3) The graphitized crude product is transferred to a screening machine and then demagnetized by a magnetic rod to obtain a graphite negative electrode material.

[0021] Example 1 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 9:1 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0022] Example 2 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 7:3 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0023] Example 3 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0024] Example 4 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 3:7 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0025] Example 5 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 1:9 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0026] Example 6 The specific steps are: (1) Medium sulfur coke with a sulfur content of 2.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material.

[0027] Example 7 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and ordinary petroleum coke were crushed in a mechanical mill to a size of D50 of 12 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 12 μm and the ordinary petroleum coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 hours; (3) Mix the pre-carbonized medium-sulfur coke and ordinary petroleum coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material with high capacity and long circulation.

[0028] Example 8 The specific steps are: (1) medium-sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 10 μm; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 10 μm and the isotropic coke raw material with a D50 of 10 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material with high capacity and long circulation.

[0029] Example 9 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to sizes of 10 μm and 14 μm, respectively; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 10 μm and the isotropic coke raw material with a D50 of 14 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material with high capacity and long circulation.

[0030] Example 10 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to sizes of 14 μm and 10 μm, respectively; (2) Pre-carbonizing and heat treating the medium-sulfur coke raw material with a D50 of 14 μm and the isotropic coke raw material with a D50 of 10 μm in a reactor at 700°C for 2 h; (3) Mix the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material with high capacity and long circulation.

[0031] Embodiment 11 The specific steps are: (1) Medium sulfur coke with a sulfur content of 1.8% and isotropic coke were crushed in a mechanical mill to a size of D50 of 14 μm; (2) Pre-carbonizing the medium-sulfur coke raw material with a D50 of 14 μm and the isotropic coke with a D50 of 14 μm in a reactor at 700 °C for 2 h; (3) Mixing the pre-carbonized medium-sulfur coke and isotropic coke in a mixer at a mass ratio of 5:5 for 0.5 h: (4) Transferring the mixed coke source into a graphitization furnace, keeping it at 2600°C for 60 h, and taking it out of the furnace after cooling; (5) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a finished graphite negative electrode material with high capacity and long circulation.

[0032] Comparative Example 1 (1) Isotropic coke was crushed in a mechanical mill to a size of D50 of 12 μm; (2) heat treating the isotropic coke raw material with a D50 of 12 μm in a reactor at 700°C for 2 h; (3) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (4) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a graphite negative electrode material.

[0033] Comparative Example 2 (1) Medium sulfur coke with a sulfur content of 1.8% is crushed in a mechanical mill to a size of D50 of 12 μm; (2) heat treating the medium-sulfur coke raw material with a D50 of 12 μm in a reactor at 700° C. for 2 h; (3) The mixed coke source is transferred into a graphitization furnace, kept at 2600°C for 60 hours, and then taken out of the furnace after cooling; (4) The graphitized material is transferred to a screening machine and then passed through a magnetic rod to obtain a graphite negative electrode material.

[0034] Using the graphite negative electrode material obtained in this embodiment and the comparative example as the working electrode, metallic lithium as the counter electrode, celgard2400 as the diaphragm, 1 mol / L LiPF6 conductive salt and DMC:DEC:EC (wt%) = 1:1:1 as the electrolyte, charge and discharge tests were carried out, and the measured electrochemical properties of the materials are shown in Table 1 as the first reversible capacity.

[0035] The negative electrode material obtained in this embodiment and the comparative example was used as the negative electrode, the electrode compaction was 1.55, and lithium iron phosphate was used as the positive electrode. A 4Ah small soft pack battery cell was designed and prepared, and the compaction performance, sticking condition, DCR value of 1C pulse 10s at 50% SOC, and cycle performance of the negative electrode material were obtained as shown in Table 1. (Since the results of normal temperature cycling are slow, the accelerated test was performed at 45°C high temperature cycling here) Table 1 Note: The order of roller sticking from light to heavy is: no roller sticking, almost no roller sticking, slight roller sticking, roller sticking, and severe roller sticking.

[0036] As shown in Table 1, it can be seen from the test results of Examples 1-5 and Comparative Examples 1-2 that although the performance of the graphite negative electrode material obtained in Examples 1-5 is better than that of the graphite negative electrode material obtained in Comparative Examples 1-2, in Examples 1-5, as the proportion of medium-sulfur coke increases, the gram capacity of the negative electrode material gradually increases, and the compaction gradually improves. The improvement of these two can improve the energy density of the battery, but the sticking situation gradually becomes serious, and the sticking roller will affect the processing yield of the pole piece preparation. Severe roller pressing will lead to low material yield. Therefore, the preferred mixing mass ratio of medium-sulfur coke and commercial coke in the present invention is 30-50%: 50-70%, and the total mass percentage is 100%. The synergistic effect of medium-sulfur coke and commercial coke within this range is better, and the mixed coke source can obtain better processing yield and cycle performance.

[0037] It can be seen from Examples 3 and 6 that when the ratio of medium-sulfur coke is constant, the increase in the sulfur content in the medium-sulfur coke will lead to a slight decrease in the capacity and cycle performance of the resulting graphite negative electrode material. However, compared with Example 3, the increase in the sulfur content of the medium-sulfur coke in Example 6 will seriously affect the sticking situation, thereby reducing the processing yield.

[0038] It can be seen from Examples 3 and 7 that the specific type of commercial coke has little effect on the cycle performance, compaction and roller sticking of the obtained graphite negative electrode material. The commercial coke can specifically be petroleum coke, coal-based coke, isotropic coke or asphalt coke.

[0039] It can be seen from Example 3 and Examples 8-11 that the compaction of medium-sulfur coke and commercial coke increases as the particle size increases, and the rolling sticking situation gradually decreases, but the DCR of the battery increases and the dynamic performance deteriorates.

[0040] Compared with Examples 1-11, the capacity retention rate of Comparative Example 1 is slightly higher, which is mainly because the compaction of the negative electrode plate is lower than that of other solutions, but its material capacity is significantly lower than that of Examples 1-11. This solution mainly obtains graphite negative electrode materials by mixing medium-sulfur coke with commercial coke raw materials, and compounding a specific proportion of medium-sulfur coke with ordinary commercial coke. The two can play an excellent synergistic effect, thereby improving the capacity of graphite negative electrode materials, thereby improving the energy density of batteries. At the same time, the processing properties of the negative electrode material, including compaction and sticking roller conditions, are adjusted by regulating the sulfur content of the medium-sulfur coke, the proportion of the medium-sulfur coke, and the particle size of the coke source. Because the present invention is only a two-component composite, the particle size, mixing ratio, pre-carbonization and graphitization reaction conditions of the two components will have a greater impact on the performance of the graphite negative electrode material. The mutual coordination between the various limited parameters ensures that a high-capacity and long-cycle graphite negative electrode material is obtained, and further expands industrial applications.

[0041] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-capacity and long-cycle graphite negative electrode material, characterized in that: The steps include: (1) Pre-carbonizing medium-sulfur coke and commercial coke respectively; (2) mixing the pre-carbonized medium-sulfur coke and commercial coke, and graphitizing them to obtain a crude graphitized product; the mixing mass ratio of the medium-sulfur coke and the commercial coke is 10-90%:10-90%, and the total mass percentage is 100%; (3) Screening and demagnetizing the graphitized crude product to obtain graphite negative electrode material.

2. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, characterized in that: The mixing mass ratio of the medium-sulfur coke and the commercial coke is 30-70%:30-70%, and the total mass percentage is 100%.

3. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, characterized in that: The pre-carbonization temperature is 300-1000° C. and the temperature is kept for 1-5 hours.

4. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The graphitization temperature is 2500-3000° C., and the graphitization time is 10-30 days.

5. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, characterized in that: The median particle size D50 of the medium-sulfur coke is 8.0 to 20.0 μm.

6. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, characterized in that: The median particle size D50 of the commercial coke is 8.0 to 20.0 μm.

7. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, 5 or 6, characterized in that: The particle size of the pre-carbonized medium-sulfur coke and commercial coke mixed is normally distributed, and the median particle size D50 is 8~14μm.

8. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1, characterized in that: The mixing time of the pre-carbonized medium-sulfur coke and commercial coke is 0.5~2h.

9. The method for preparing a high-capacity and long-cycle graphite negative electrode material according to claim 1 or 8, characterized in that: The commercial coke is petroleum coke, coal-based coke, isotropic coke or asphalt coke.

10. A graphite negative electrode material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for producing natural needle coke composite graphite anode material

    CN106169582B

  • Preparation method of high-capacity long-circulation synthetic graphite negative electrode material

    CN107039654A

Cited By

  • Preparation method of long-circulation artificial graphite negative electrode material and graphite negative electrode material

    CN121097074A

  • A method for preparing a long-cycle artificial graphite anode material and the graphite anode material.

    CN121097074B

  • Graphite negative electrode material and preparation method and application thereof

    CN121097075A